The contributions of Maurício Tragtenberg: the delinquency of education in Brazil - Rodrigues, Fabiana de Cássia (Argumentum, 2022)
This article presents the way Maurício Tragtenberg approached the relationship between power and the production of knowledge. His ideas give support to the concept of academy delinquency, which demonstrates the disconnect between means and ends within education. In other words, it is a historical reality in which all teach, and the production of knowledge does not question the for what of their activities. Consequently, they reproduce the unequal power relationships and does not consider the concrete necessities of subordinate classes in unequal and combined capitalism development. The strategies to confront these conditions are discussed from a class struggle perspective. The texts about education, written by the author during the transition to the “New Republic”, and especially the ones produced for the educational journal Educação & Sociedade, are the main sources. Accordingly, Tragtenberg’s ideas, the reality of his thoughts, are discussed to inspire the analysis of contemporary educational problems.